Dynamics and Existence of Angkong in East Sumatra - Rudiansyah Rudiansyah (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2022)
This paper reviewed the 'Dynamics and Existence of Angkong in East Sumatra'. Angkong is one of the public transportation used during the Dutch East Indies period in East Sumatra. This transportation is also known as the Hong Kong rickshaw. Humans formerly pulled it by running. These human-drawn angkong were generally brought indirectly by the Chinese who worked on the plantations. As Viktor Purcell wrote, most Chinese worked in the logging industry and as angkong porters. Before this, other forms of transportation were used, such as horse-drawn carriages, ox-carts, or buffalo carts. These kinds of transportation were used for special needs, such as in forest areas, and as a means to enter plantation areas that gardeners used at that time. This research intended to explain the dynamics and existence of rickshaw transportation in East Sumatra using the desk research method on research reports, various sources of books, journals, and related articles. This research also utilized the historical explanation theory from Kuntowijoyo. The distribution of angkong in East Sumatra did not immediately become public transportation but started from private ownership. It started with the gardeners seeing and supervising the plantations they manage.